Capacity comparison of MIMO and cooperative MIMO - Kumar Sarangi, Ashish; Mukherjee, Amrit; Datta, Amlan (International Journal of Engineering and Technology, 2017)
To achieve high capacity and high data rates is the main requirement for todayâ€™s generation. This paper studies about the performance and capacity comparison of MIMO and cooperative MIMO systems. The comparison of capacity between multiple- input- multiple- output (MIMO) and cooperative MIMO systems helps us to know that which system have better performance and better capacity. The simulation results shows that among SISO, SIMO, MISO and MIMOÂ system the capacity of MIMO will be better but in between MIMO and cooperative MIMO, Cooperative MIMO system have high capacity than MIMO systems.Â Â